CHAINS OF CIRCUMSTANCE: REALISM AND NATURALISM IN TESS AND SISTER CARRIE - Qizi, Mamatova Dilorom A’zam qizi (PT. Antis International Publisher, 2025)
Objective: This study aims to examine the convergence of Realism and Naturalism through the comparative analysis of Thomas Hardy’s Tess of the d’Urbervilles and Theodore Dreiser’s Sister Carrie, focusing on how female protagonists are shaped by social, economic, and personal forces. Method: The research employs a comparative literary analysis that explores thematic concerns, narrative techniques, and character development across the two novels within their distinct cultural and historical contexts. Results: The findings reveal that Hardy’s Tess is situated in the moral and social frameworks of Victorian England, where fate and societal judgment dictate her tragic destiny, while Dreiser’s Carrie reflects the American Naturalist tradition of social mobility, material ambition, and moral ambiguity. Despite their differences, both authors depict women as products of their environments who simultaneously challenge societal constraints. Novelty: This study contributes to literary scholarship by demonstrating how Realism’s detailed representation of everyday life and Naturalism’s deterministic outlook converge in portraying women’s roles, offering new insights into cross-cultural interpretations of gender, morality, and social change at the turn of the century.